Proposed Business Solutions for Small Business Development (Case Study : Calisa Beauty Care) (The Indonesian Journal of Business Administration, 2021)
Calisa Beauty Care (Calisa) is local small beauty care business Berau, East Kalimantan, focused on face skin care and servicing only women. Calisa business started at home in 2018 service marketed by “word of mouth” on small community. In the beginning of 2019, Calisa open its first store, in the first 4 months customer visiting rise to 2.9 times, but after May 2019, the customer visiting decreased. On February, 2020, Calisa Beauty Care faced a legal problem that has negative effect to Calisa Beauty Care brand image. To solve the problem, researcher analyzed using Porters Five Forces, competitors analysis, customers analysis, SWOT analysis, and TOWS matrix.Keywords: Calisa Beauty Care, local business, Berau, visiting decreased, IPA Matrix